2015
DOI: 10.1002/cbin.10438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression profiles reveals the regulatory network of cold‐inducible RNA‐binding protein mediating the growth of BHK‐21 cells

Abstract: Cold-inducible RNA-binding protein (Cirp), the first cold-shock protein identified in mammals, is a sensor protein whose expression increases in response to stress. Recent reports have shown that Cirp is involved in cell proliferation, development, circadian modulation under physiological conditions, and tumor formation and progression. However, the molecular mechanisms underlying the activities of Cirp in the mammalian kidney cells remain unclear. In this study, we constructed BHK-21cells overexpressing Cirp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This was also suggested by experiments in ref. 60, which found that a specifically cold-sensitive RNA-binding protein influences circadian transcription in mice, as well as prior work examining circadian responses to cold temperatures (61,62).…”
Section: Resultsmentioning
confidence: 88%
“…This was also suggested by experiments in ref. 60, which found that a specifically cold-sensitive RNA-binding protein influences circadian transcription in mice, as well as prior work examining circadian responses to cold temperatures (61,62).…”
Section: Resultsmentioning
confidence: 88%
“…CIRBP, which is the first cold-shock protein identified in mammals, was recently identified as a proinflammatory cytokine (22). As a sensor protein, which expression increases in response to stress, CIRBP plays important roles in tumor recurrence (23,24). A study by Zhang et al (25) has shown that CIRBP plays key roles in hypoxia-induced cell cycle arrest and may be utilized for preventing hypoxia-induced neonatal brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that post‐transcriptional biological activities contribute up to 33.15% of the total variation of RNA‐protein correlations (Wu et al, ). Recent in vitro and in vivo RNA binding protein identification studies have enabled us to start in‐depth explorations of the principles governing post‐transcriptional control in regulating important pluripotency factors through identifying their RBPs (Henics et al, ; Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%